Evaluasi Implementasi “POMP” Filariasis terhadap Perubahan Aspek Pengetahuan, Lingkungan dan Perilaku Penderita Filariasis - Irfan Irfan; Israfil Israfil; Marieta Kristina Sulastiawati Bai (JURNAL INFO KESEHATAN, 2019)
Filariasis is an infectious disease caused by filarial worms and transmitted by mosquitoes. Efforts to suppress the case of filariasis are eliminated through the administration of filariasis Mass Drug Prevention (MDP). The filariasis MDP program in Ende Regency has been conducted since 2011-2015, and the first phase evaluation was conducted in 2017. This study aims to find a picture of community knowledge about the filariasis elimination program in Ende Regency, to find a picture of behavioral change and environmental management after the implementation of the filariasis elimination program. This research is qualitative research with an ethnographic approach. There were 20 informants consisting of 10 sufferers, 5 patients' families, 3 health workers, and 2 village officials. The results showed that almost all informants had known the Filariasis MDP program and had taken the filariasis drug. Most informants still had behaviors that were at risk of filariasis. The environment where the informant lives did not have a risk for filarial worm breeding. The conclusion of the research shows that the success in handling and preventing filariasis in Detusuko and Welamosa villages are supported by the community's understanding of the MDP program and consuming filariasis medicine, vanishing filarial mosquito breeding places. However, it was still found that community behavior has not changed which are activities outside the home at night, not using long-sleeved clothes and the habit of hanging dirty clothes.